ASSESSING THE EFFECTIVENESS OF DIGITAL PRESENCE ENHANCEMENT THROUGH PRIMARY SURVEY OF USERS AND CLIENTS - Bimbh, Preet; George, Linu (International Journal of Engineering Technologies and Management Research, 2025)
The aim of this study is to gauge the effectiveness of digital presence enhancement strategies through a primary survey conducted on users and clients. Organizations nowadays use digital platforms increasingly for creating brand visibility, engaging target audiences, and building better service delivery. This research assesses how far users and clients perceive these digital initiatives in terms of website usability, social media engagement, relevance of content, and overall online experience. Primary data was generated through a structured questionnaire, and the findings have outlined the major strengths and gaps in existing digital practices. This study established that an enhanced digital presence positively influences customer satisfaction, trust, and brand preference. At the same time, it has also identified weak spots that need amendment for effective engagement. Results give actionable insight to managers and businesses looking to optimize their digital strategies and firm up their online footprint.